Historia Apollonii Regis Tyri, ed. de Gareth Schmeling, Leipzig, Teubner, Verlagsgesellschaft, 1988, XXXI + 143 pp. ISBN 3-322-00450-3 (Minerva. Revista de Filología Clásica, 2019)
Reseña de Historia Apollonii Regis Tyri, ed. de Gareth Schmeling, Leipzig, Teubner, Verlagsgesellschaft, 1988, XXXI + 143 pp. ISBN 3-322-00450-3